Distribution of selenium in surface waters of Tibet and environmental impact factors that determine its concentration. (February 2022) - Zha, Xinjie; Tian, Yuan; Yu, Chengqun; Xiao, Jianyu
Graphical abstract: Highlights: Amount and distribution of selenium (Se) in surface waters across Tibet are studied. Study explores the relationship between Se concentration and environmental factors. Separate and combined influences of 10 environmental impact factors are considered. Contribution of factors and their internal subzones are quantitatively analyzed. Identified 5 main environmental indicators that influence water Se concentration. Abstract: Selenium (Se) is essential for human health. Its concentration in surface water is determined by diverse environmental factors. However, few studies have discussed the distribution of the surface water Se concentration in Tibet; quantitative analysis of how multiple environmental impact factors affect the distribution of surface water Se concentration is also lacking. In this study, the relationship between surface water Se concentration and environmental indicators is investigated in a broad scope by chemical examination, and the spatial distribution of 702 surface water samples across 66 counties in Tibet is comprehensively analyze. The principle of spatial stratified heterogeneity is used not only to measure the individual or interactive influences of 10 potential environmental impact factors, but also to identify the highest potential impact types or ranges of each factor. Results show that the surface water Se concentrations in Tibet are very low, with a mean value of 0.519 ± 0.551 μg/L (range of 0–3.944 μg/L). Spatially, surface water Se concentrations exhibited a reducing trend toward the central and southeast parts of Tibet. In general, surface water in desert areas with low precipitation, which feature alkaline soil environments and magmatic rock outcrops, had higher Se concentration, while overall, the temperature and geographical environment showed little impact on surface water Se concentration. This study contributes to a better understanding of the spatial distribution and environmental impact mechanism of surface water Se concentration in Tibet, and provides baseline indicators for the establishment of a prediction model for the distribution of Se in surface water based on spatial characteristics.